Aspek Hukum Perlindungan Konsumen dalam Menghadapi Praktik Overclaim Kandungan Produk Skincare: Analisis Kesesuaian dengan Hasil Uji Laboratorium - Sinta Rahmawati; Sutarman Yodo; Adiguna Kharismawan (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2026)
The rapid growth of Indonesia’s skincare industry has led to an increase in overclaim practices, in which product content or claimed benefits do not correspond to laboratory test results. This practice potentially harms consumers and violates Law Number 8 of 1999 on Consumer Protection and regulations issued by the Indonesian Food and Drug Authority (BPOM). This research employs a normative juridical method using statutory, conceptual, and case study approaches to examine overclaim violations during 2023–2025. The results indicate that overclaim practices violate Articles 4, 7, 8, 9, and 10 of the Consumer Protection Law, as well as BPOM regulations requiring scientifically valid and accountable product claims. Laboratory findings reveal significant discrepancies between the declared and actual active ingredient contents, demonstrating misleading information that may harm consumers. Although the existing legal framework provides comprehensive protection, its effectiveness remains constrained by weak oversight of digital marketing practices and low levels of consumer legal literacy. Legal protection is available through BPOM administrative sanctions, dispute resolution through the Consumer Dispute Settlement Agency (BPSK), and civil and criminal legal remedies. Strengthening supervision, consumer education, and business compliance is therefore essential to ensure effective consumer protection.